Translation of Physical Aspects of Women Image From Indonesian Into German: An Appraisal Analysis - Cicu Finalia (Universitas Padjadjaran, 2022)
This study discusses the translation of aspects of physical image related to image of women in Eka Kurniawan’s “Lelaki Harimau” novel into German, and describes the types of attitude associated with the physical image of women. Using Martin & Rose’s theory of appraisal (2007) and Molina & Hurtado Albir’s theory of translation techniques (2002), aspects of physical image compiled grammatical items, lexical items or metaphors related to image of women in the novel into domains to classify the aspects of physical image and the translation techniques used to translate the aspects of physical image. From the results of the initial and earlier discussion it was found that the translator of the novel “Lelaki Harimau” into German are using nine translation techniques – mostly established equivalent and modulation. The use of these certain translation techniques is one indicator that translation technique determines the image shifting.